(untitled) (Revista de Estudos da Linguagem, 2019)
Abstract: This paper explores the interpretation of bare singulars (count nouns that are not preceded by determiners) as coche (“car”) in María compró coche ayer (“Mary bought (a/some) car(s) yesterday”) in Mexican Spanish. A quantity judgment task was performed with 134 L1 Mexican speakers and they had to choose one between two scenarios where different quantities of the tested noun were shown. In this task, while presenting two different characters, one that has two big portions of x (Volume) and another that has six different portions of x (Number), it is presented a comparative sentence (Marcelo tiene más X que Lena (“Marcelo has more X than Lena”)) and asked whether the sentence was true or false given the context. The results show that a Number interpretation was preferred for bare singulars (Marcelo tiene más bici que Lena (“Marcelo has more bike than Lena”)) and a Volume interpretation was preferred for substance mass nouns (Marcelo tiene más agua que Lena (“Marcelo has more water than Lena”)). That is, the absence of the plural morpheme (mass syntax) does not trigger a mass interpretation of bare singulars; bare singulars are interpreted as pluralized count nouns even when they are not pluralized. Keywords: Mexican Spanish; bare singulars; count/mass distinction; quantity judgment task. Resumo: Esse trabalho explora a interpretação de singulares nus (nomes contáveis que não são precedidos de determinantes) como coche (“carro”) em María compró coche ayer (“Maria comprou (um/alguns) carro(s) ontem”) no Espanhol Mexicano. Um julgamento de quantidade foi feito com 134 falantes mexicanos L1 e eles tiveram que escolher um entre dois cenários em que diferentes quantidades do nome testado eram mostradas. Nessa tarefa, enquanto duas personagens diferentes foram apresentadas, uma que possuía duas porções grandes de x (Volume) e outra que possuía seis diferentes porções de x (Número), é apresentada uma sentença comparativa (Marcelo tiene más X que Lena (“Marcelo tem mais X que Lena”)) e perguntado se a sentença é verdadeira ou falsa, dado o contexto. Os resultados mostram que a interpretação de Número foi a preferida para singulares nus (Marcelo tiene más bici que Lena (“Marcelo tem mais bicicleta que Lena”)) e a interpretação de Volume foi a preferida para nomes massivos de substância (Marcelo tiene más água que Lena (“Marcelo tem mais água que Lena”)). Isto é, a ausência de morfema de plural (sintaxe massiva) não desencadeia uma interpretação massiva de singulares nus; singulares nus são interpretados como nomes contáveis pluralizados mesmo que eles não estejam pluralizados. Palavras-chave: Espanhol Mexicano; singulares nus; distinção contável/massiva; tarefa de julgamento de quantidade.